HIV and HCV augments inflammatory responses through increased TREM-1 expression and signaling in Kupffer and Myeloid cells. - Jinhee Hyun; Robert S McMahon; Anna L Lang; Jasmine S Edwards; Alejandro Dmitar Badilla; Morgan E Greene; Geoffrey W Stone; Suresh Pallikkuth; Mario Stevenson; Derek M Dykxhoorn; Shyam Kottilil; Savita Pahwa; et al. (PLoS Pathogens, 2019)
Chronic infection with human immunodeficiency virus (HIV) and hepatitis C virus (HCV) affects an estimated 35 million and 75 million individuals worldwide, respectively. These viruses induce persistent inflammation which often drives the development or progression of organ-specific diseases and even cancer including Hepatocellular Carcinoma (HCC). In this study, we sought to examine inflammatory responses following HIV or HCV stimulation of macrophages or Kupffer cells (KCs), that may contribute to virus mediated inflammation and subsequent liver disease. KCs are liver-resident macrophages and reports have provided evidence that HIV can stimulate and infect them. In order to characterize HIV-intrinsic innate immune responses that may occur in the liver, we performed microarray analyses on KCs following HIV stimulation. Our data demonstrate that KCs upregulate several innate immune signaling pathways involved in inflammation, myeloid cell maturation, stellate cell activation, and Triggering Receptor Expressed on Myeloid cells 1 (TREM1) signaling. TREM1 is a member of the immunoglobulin superfamily of receptors and it is reported to be involved in systemic inflammatory responses due to its ability to amplify activation of host defense signaling pathways. Our data demonstrate that stimulation of KCs with HIV or HCV induces the upregulation of TREM1. Additionally, HIV viral proteins can upregulate expression of TREM1 mRNA through NF-кB signaling. Furthermore, activation of the TREM1 signaling pathway, with a targeted agonist, increased HIV or HCV-mediated inflammatory responses in macrophages due to enhanced activation of the ERK1/2 signaling cascade. Silencing TREM1 dampened inflammatory immune responses elicited by HIV or HCV stimulation. Finally, HIV and HCV infected patients exhibit higher expression and frequency of TREM1 and CD68 positive cells. Taken together, TREM1 induction by HIV contributes to chronic inflammation in the liver and targeting TREM1 signaling may be a therapeutic option to minimize HIV induced chronic inflammation.